If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4z + -5) = 6 + -1(7 + -2z) Reorder the terms: 3(-5 + 4z) = 6 + -1(7 + -2z) (-5 * 3 + 4z * 3) = 6 + -1(7 + -2z) (-15 + 12z) = 6 + -1(7 + -2z) -15 + 12z = 6 + (7 * -1 + -2z * -1) -15 + 12z = 6 + (-7 + 2z) Combine like terms: 6 + -7 = -1 -15 + 12z = -1 + 2z Solving -15 + 12z = -1 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -15 + 12z + -2z = -1 + 2z + -2z Combine like terms: 12z + -2z = 10z -15 + 10z = -1 + 2z + -2z Combine like terms: 2z + -2z = 0 -15 + 10z = -1 + 0 -15 + 10z = -1 Add '15' to each side of the equation. -15 + 15 + 10z = -1 + 15 Combine like terms: -15 + 15 = 0 0 + 10z = -1 + 15 10z = -1 + 15 Combine like terms: -1 + 15 = 14 10z = 14 Divide each side by '10'. z = 1.4 Simplifying z = 1.4
| a^2-6a+5=0 | | 10a-20=5a+80 | | 10y+5=18 | | 8a-40=4a+60 | | 8(A-5)=70 | | 7B-70=140 | | 18-2x=x^2-5 | | 18-2x=x^2-25 | | 3t^2-8t+2=0 | | 6b-80=160 | | 4(x-1)+12+2x=6x-40+2(30-x)-2 | | 6+4(x+2)+2x-3=2x+27 | | 4(x+3)+x=11 | | 7x-13=59-5x | | 9x-3=2x+11 | | 6x+3-2x-1=14 | | 12+6x-3+x+7-3x=32 | | 7w^2+6w+7=0 | | 4s^2-15s+9=0 | | -11+(-10)= | | 6(t-3)+8t=7(2t+3)-13 | | 0=26 | | 1+-6= | | 7x-3=4.5 | | 0.5(5x+8)=0.5x | | x^2-12x+36=4x+4 | | 3(x+8)=1+3x | | 0.125(x-16)=0 | | 2w^2+5w-3=0 | | 7d-3d+6d+3=3d | | 0.25x-1=1 | | 4x^2-8x+0=0 |